The Use of Continuous Glucose Monitoring Systems in the Diagnosis and Monitoring of Gestational Diabetes Mellitus and Diabetes in Pregnancy - A Review of the Literature - Lenart, Kacper; Kwaśna, Julia; Załęska, Adrianna; Bednarek, Szymon; Kaźmierczyk, Izabela; Górski, Mateusz; Homza, Michał; Bychowski, Mateusz; Zakrzewska, Natalia; Kulicka, Joanna (Quality in Sport, 2024)
Background: Gestational diabetes mellitus (GDM) and preexisting diabetes present significant risks to maternal and neonatal health. Continuous glucose monitoring (CGM) has emerged as a valuable tool for optimizing glycemic control during pregnancy, offering real-time data and insights beyond traditional methods. Objective: This review evaluates the role of CGM in the management and diagnosis of diabetes during pregnancy, focusing on its clinical efficacy, impact on maternal and neonatal outcomes. Methods: A systematic literature search was conducted, covering studies published between 2017 and 2024. Inclusion criteria targeted studies assessing CGM in pregnant populations with GDM, T1D, or T2D. Data were synthesized to highlight maternal glycemic control metrics, neonatal outcomes, and limitations of CGM use. Results: CGM, particularly real-time CGM (rt-CGM), significantly improves maternal glycemic control. Enhanced glycemic management has been associated with reduced risks of large-for-gestational-age (LGA) births, macrosomia, and preeclampsia, particularly in women with T1D. Conclusion: CGM is a transformative tool in managing diabetes during pregnancy, providing critical insights into glycemic trends and enabling personalized care. While its benefits in improving maternal outcomes are clear, further research is needed to ensure equitable access.